Educação profissional no Estado do Ceará: análise do perfil dos alunos dos cursos do SENAC-CE - Sousa, Railane Porfirio de (2021)
This study aimed to characterize the profile of students in professional education courses held at Senac-Ce from 2017 to 2019. Professional education is divided into three modalities, professional qualification; high school technician and technological graduation/postgraduate. In this study, only the first two were addressed, due to the absence of enrollments in the Institution in the technological undergraduate/graduate course in the analyzed period. Data collected through reports from the Senac-Ce educational system revealed social and academic information about students enrolled in the period. On the methodological aspects, a qualitative descriptive study was used. Analyzing the results, it can be inferred that in professional qualification courses and high school technicians the highest prevalence is of women, young people and those who had completed high school, with a greater demand in the areas of Management and Business and Environment and Health. As for the achievement, the professional qualification was satisfactory, with more than 80% approval, while the technical courses of high school had a high rate in relation to evasion around 20%. In the period analyzed, the students' social and academic profile was uniform, with a strong predominance of female participation.